THE ARCHITECTURE OF CLOUD COMPUTING FOR EDUCATIONAL ENVIRONMENT IN INDONESIA - Baginda Anggun Nan Cenka; Zainal A. Hasibuan; Heru Suhartanto (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2012)
Information and Communication Technology (ICT) based Education has become a new trend in education of Indonesia. Nowadays, the number of educational institution have implemented this practice for their environment as supporting educational processes is more increasing. However, there are several factors inhibiting this implementation such as: inadequate infrastructure, not well integrated service, lack of competence in managing, and the standardization of the implementation strategy was needed. At the same time, Cloud computing has been a hot topic and a new business paradigm for education. Cloud computing is closely related to provision large resource computation which can provide added values for educational environment. In this paper, we introduce the architecture of cloud technology for educational environment to accommodate all interests and needs in this area. The architecture was designed based on Cloud taxonomy that provide flexibility, customizability, extensibility, and reusability that fit the dynamic educational environments.